2016
DOI: 10.1080/02713683.2016.1214970
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rabbit Corneas Subjected to Stromal Stiffening by the Açaí Extract (Euterpe oleracea)

Abstract: The açaí extract was effective in promoting CXL in rabbit corneas as characterized by the different techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…The elastic modulus was 10.5 times higher in corneas treated with 4% açaí extract for 2h than in those in the control group [7].…”
Section: Introductionmentioning
confidence: 74%
“…The elastic modulus was 10.5 times higher in corneas treated with 4% açaí extract for 2h than in those in the control group [7].…”
Section: Introductionmentioning
confidence: 74%
“…Slusarewicz et al [28] comparing the efficiency of seven compounds in collagen crosslinking observed that the PA were very efficient and reacted rapidly with the tissue. In addition, Bersanetti et al [29] showed that the ac ¸aı ´extract is efficient to promote an increase in the denaturation temperature and enthalpy of rabbit corneas.…”
Section: Resultsmentioning
confidence: 99%
“…Various photoactivated cross-linkers other than riboflavin include rose bengal, Eosin Y, and WST-D, all of which are excited by different spectra of light. 81 Among the previously reported chemical cross-linkers genipin, 82 glyceraldehyde, 83 glutaraldhyde, 84 Açaí Extract, 85 formaldehyde releasers, 86 decoron, 87 and nitroalcohols 88 have been explored for use in corneal or scleral cross-linking. These agents do not require exposure to irradiance to be activated, but none of them has been translated into clinical practice.…”
Section: Advances In Treatmentmentioning
confidence: 99%